THE EFFECT OF INCREASING IRON FIBER OF LATHE ENGINE WASTE IN PRESSURE STRENGTH AND PULL STRENGHT OF CONCRETE SLIT - Vansprik Hurowura; Samuel Layang (Jurusan Pendidikan Teknologi Dan Kejuruan, 2015)
Many research which has been done with a fiber in normal concrete fusion to increase the concrete press strengthespecially on the weakness of concrete quality on tensile strength. In Indonesia, steel and iron fiber utilitization (bendrat wire) on concrete fusion not yet to be known. Besides, making fiber suffered high cost especially making steel fiber that is very difficult because they have to be imported. To solve this problem, in this research iron fiber lathe engine waste that easy to find and more economic is used to change the steel and iron fiber utilization. It uses iron fiber lathe engine waste with a lenght of Â± 6 cm and diameters of Â± 8 mm, with the edges bent and with the presentate of 0%, 2%, 4%, 6%, and 8% to cement weight. For concrete without any improvement of iron fiber classified as the concrete with 0% iron fiber with the pressure trenght on f'c 25 MPa. The test speciment used in this reseach has cylinder shape and has 15 cm diameters and 30 centimeters on high. Test was arranged when it has been 14th and 28th days of curing to know the effect of iron fiber in compressive strength and tensile strength and increment percentage of iron fiber on lathe engine waste that is the most optimum. The result of research shows that the increasing of iron fiber on lathe engine waste on concrete fusion gives the effect of compressive strength and tensile strength, increase compressive strength of concrete on 46,64% on 14th day and 45,45% on 28th and increasing the compressive strength of concrete on 15,07% on 14th day and 23,07 % on 28th, compared with concrete without fiber has 8% on 14th and 28th. On 14th has 12,54 MPa compressive strength and 13,63 MPa on 28th whereas on 14th has 1,45 MPa tensile strength and 1,6 MPa on 28th. Althought the result of the test of compressive strength and pulling slit concrete showed an improvement but it has not yet to reach the target valve 25 MPa, because of several factor whether it is on physical factor, building process, maintenance,and the test and its equipment for research that has not to be perfect yet.